Transumbilical single-site double-port laparoscopic appendectomy in children. Report of a single center experience with comparison with three-port laparoscopic appendectomy - Qin, Hong; Liu, Hongzhen; Xia, Tian; Tang, Bingqiang; Zhang, Shisong; Wang, Lulu (Frontiers in Pediatrics, 2025)
ObjectiveTransumbilical single-site double-port laparoscopic appendectomy (TSSDPLA) represents an innovative and minimally invasive approach for managing acute appendicitis. This study aims to compare the clinical outcomes of TSSDPLA vs. three-port laparoscopic appendectomy (TPLA) in a pediatric series.MethodA retrospective analysis was conducted between July 2023 and July 2024 at the Department of General Surgery, Children's Hospital affiliated to Shandong University. The patients were categorized into two groups: the TSSDPLA group and the TPLA group. Outcomes including patient demographics, leukocyte count upon arrival, duration of the operation, costs associated with the operating room, and any complications encountered.ResultsThe results indicated no significant differences between the TSSDPLA and TPLA groups in terms of age, gender, leukocyte counts, liquid diet, length of hospital stay, pathology or complications. However, the mean operating room costs were significantly lower in the TSSDPLA group (p < 0.001). Additionally, the mean operation time for the TSSDPLA group was marginally longer compared to the TPLA group.ConclusionsTSSDPLA is a reliable technical technique for the management of acute appendicitis. This approach offers several advantages, including improved cosmetic outcomes, reduced surgical trauma, and lower costs.